LOVING NATION, ENDORSING THE ECCLESIAL UNIVERSAL: A ROMANIAN PERSPECTIVE - MUCICHESCU, Paul Andrei (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2020)
This theological and philosophical article aims for a solution to the provocation of nationalism and offers a series of interconnected arguments for this purpose. In doing so, it makes use of Romanian cultural realities and sources (stances of Dumitru Stăniloae, of Daniil Sandu Tudor and others, as well as dictionary entries). The considerations start from the topic of politics and of what politics consists of – ideology. Turning towards ecclesiology and social theology, the relationship between hate and phyletism is assessed. Considering this relationship, the analysis shows that, from an Orthodox point of view, true nationalism should be understood as a form of love – corruptible but legitimate. Ideological nationalism is identified as its opposite. The Gordian Knot of ideological nationalism is found to be a false understanding of national interests. Finally, a second relation is investigated – the one between the national and the universal, seen from Romanian premises.